قواعد نقد المتن عند الشيخ عبد الله بن الصديق الغماري من خلال كتابه الفوائد المقصودة - غريسي علي (University of Eloued جامعة الوادي, 2024)
"يتناول هذا البحث قضية من القضايا المهمة وهي نقد المتن عند المحدثين، حيث بينت في المبحث التمهيدي نشأته وتطوره واهتمام المحدثين وعنايتهم به ومثلت بنماذج من نقد المتن عند السلف من الصحابة التابعين ومن بعدهم من المحدثين،كما تطرقت إلى التّعريف بالشيخ عبد الله بن الصديق الغماري ونشأته ومكانته في علم الحديث ومؤلفاته وكذا التعريف بكتابه ""الفوائد المقصودة في بيان الأحاديث الشاذة المردودة"". ثم تناولت في باقي المباحث القواعد التي أعملها حتى حكم على الحديث بالشذوذ، وبينت القواعد التي انفرد بها متبعا في ذلك المنهج الاستقرائي التحليلي. وخلصت في نهاية البحث إلى بعض النتائج والتي من أهمها ثبوت علم نقد المتن وظهوره منذ زمن النبوة وامتداده عبر العصور إلى يومنا هذا وأنه علم دقيق لا يتأهل له إلا الحفاظ المهرة والمحدثون الصيارفة، وأن هناك قواعد مشى عليها المحدثون خلال نقدهم للمتن ومسالك سلكوها قبل ردهم للحديث. "This research deals with one of the important issues, which is the criticism of the text according to the hadith scholars. In the introductory section, I showed its origin and development, and the interest and care of the hadith scholars, and it was represented by examples of text criticism among the predecessors of the Companions, the Successors, and the hadith scholars after them. I also touched on the introduction to Sheikh Abdullah bin Al-Siddiq Al-Ghumari and his upbringing. And his place in the science of hadith and its writings, as well as the introduction to his book “Al-Fawaid Al-Maqsud fi Bayan Al-Ahadith Al-Iddah Al-Murdawdoo’”. Then, in the rest of the sections, I discussed the rules that I used until the hadith was judged to be abnormal, and I explained the rules that were unique to me, following the inductive and analytical approach. At the end of the research, I concluded some results, the most important of which is the proven science of text criticism and its emergence since the time of prophecy and its extension through the ages to the present day, and that it is an accurate science that only skilled memorizers and modern hadith scholars are qualified for, and that there are rules that the hadith scholars followed during their criticism of the text and paths they took before their response to the hadith. . "
مذكرة ماستر
Keywords: النقد، المتن، المسالك، الغماري.; criticism; text; tracts; Al-Ghumari.